Serum and follicular fluid organochlorine concentrations among women undergoing assisted reproduction technologies - Ryan Louise; Vitonis Allison F; Altshul Larisa; Missmer Stacey A; Meeker John D; Cramer Daniel W; Hauser Russ (BMC, 2009)
Abstract Background Exposure to persistent organic pollutants, including polychlorinated biphenyls (PCBs) and organochlorine pesticides, is widespread among the general population. There is evidence of adverse effects on reproduction and early pregnancy in relation to organochlorine exposure but human studies remain limited. The increased use of assisted reproductive technologies (ART) presents unique opportunities for the assessment of environmental influences on early pregnancy outcomes not otherwise observable in humans, but studies need to be designed to maximize the efficiency of the exposure data collected while minimizing exposure measurement error. Methods The present study was conducted to assess the correlation between concentrations of organochlorines in serum and follicular fluid samples collected from a subset of women undergoing ART in a large study that took place between 1994 and 2003, as well as the temporal reliability of serum organochlorine concentrations among women undergoing multiple ART cycles in the study. PCB congeners (118, 138, 153, and 180), 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (p,p'-DDT), the DDT metabolite p,p'-DDE, hexachlorobenzene (HCB), oxychlordane, trans-nonachlor and mirex were measured in 72 follicular fluid samples and 265 serum samples collected from 110 women. Results Organochlorine concentrations in paired serum and follicular fluid samples were correlated, with Pearson and Spearman coefficients ranging from 0.60 to 0.92. Serum organochlorine concentrations were two- to three-fold greater than in follicular fluid, and a significant inverse trend was observed in the distribution of follicular fluid:serum ratios with increasing molecular weight of the compound (p-value for trend < 0.0001). Serum organochlorine concentrations were highly reliable over the course of several months, with intraclass correlation coefficients ranging from 0.86 to 0.98. Finally, there was evidence for a declining trend in organochlorine concentrations between samples collected between years 1994-1998 and those collected in 1999-2003. Conclusion Our results support the use of a single serum sample to adequately represent a more biologically relevant dose (concentrations in follicular fluid), as well as exposure levels over time, in epidemiological studies of ART outcomes in relation to organochlorine exposure.